Pregnancy‐Related Aortic Dissection—A Rare Complication of Pregnancy - Mohammad Baseem Shaikh; Reagan Michelle Stafford; Erinn Ogburn; Samuel Tyagi (Clinical Case Reports)
ABSTRACT Patients with pregnancy‐related aortic dissections should be transferred to high‐volume aortic centers for management. Malperfusion syndromes from acute type A aortic dissections appear to have better outcomes with thoracic endovascular repair before definitive surgical repair.